Freiheit zu ökumenischer eucharistischer gastfreundschaft/zur offenen kommunion - H. H. Eßer (Acta Theologica)
The paper is pleading for ecumenical liberty in favour of an epicletic-pneumatological understanding of the Lord’s Supper. After a short review of the last 70 years in the Protestant/Roman Catholic ecumenical relation in this regard, the main part treats the following: The presence of Christ in Word and Sacrament tending to the rediscoveryof the Epiclesis. The final position is founded in an epicletic prayer of the so called ‘kurpfälzische Kirchenordnung 1563’, that underlines the fundamental liturgical unity of the essentials of the Eucharist: 1) The institution by the Lord, 1 Cor 11:23-25; 2) The interpretation of St. Paul, 1 Cor 11:26; 3) The invitation to Holy communion, Lc 14, 17 / Ps 34,9. This means unity in rite administrare (CA VII).